2020
DOI: 10.3389/fpsyt.2020.551952
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of Magnetoencephalography Resting-State Functional Connectivity in Schizophrenia

Abstract: The reliability of magnetoencephalography (MEG) resting-state functional connectivity in schizophrenia (SZ) is unknown as previous research has focused on healthy controls (HC). Here, we examined reliability in 26 participants (13-SZ, 13-HC). Eyes opened and eyes closed resting-state data were collected on 4 separate occasions during 2 visits, 1 week apart. For source modeling, we used minimum norm software to apply dynamic statistical parametric mapping. Source analyses compared the following functional conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Our results demonstrate that between ImCoh and PDC inward consistently exhibit significant differences in EZs vs non-EZs when DLS is stable over 3 consecutive days. Similarly, other studies using MEG and resting-state scalp EEG have demonstrated that ImCoh has varied test-retest reliability depending on the brain network tested in patients with schizophrenia 22 and controls. 23 Also, in a study measuring FC in controls using MEG, PDC was the most robust directed measure.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our results demonstrate that between ImCoh and PDC inward consistently exhibit significant differences in EZs vs non-EZs when DLS is stable over 3 consecutive days. Similarly, other studies using MEG and resting-state scalp EEG have demonstrated that ImCoh has varied test-retest reliability depending on the brain network tested in patients with schizophrenia 22 and controls. 23 Also, in a study measuring FC in controls using MEG, PDC was the most robust directed measure.…”
Section: Discussionmentioning
confidence: 76%
“…Evaluation of SEEG FC stability over time or as a function of ASM dosage is limited, 20,21 although ImCoh and PDC metrics have demonstrated stability in magnetoencephalography (MEG) and scalp EEG studies. [22][23][24] Time and spectral domain features of intracranial EEG (iEEG) fluctuate, but previous studies demonstrated no significant difference in prediction of surgical outcomes with 1-hour time segments collected >4 hours apart or a difference between 1-hour segments and shorter segments as brief as 10 seconds. 21,25 Whereas one study demonstrated decreased cortical activity after ASM weaning in iEEG, 26 effects of ASMs on SEEG FC measures have not been formally studied.…”
Section: Discussionmentioning
confidence: 99%
“…The sFNC approach ascertains connectivity patterns based on a single connectivity or correlation value across the time analyzed which can often be as long as 5–10 min. While this approach has yielded reliable resting‐state networks (Candelaria‐Cook & Stephen, 2020; Dinis Fernandes et al, 2020; Franco et al, 2013; Li et al, 2018), it is more likely that functional connectivity changes over short segments of time due to dynamic (time‐varying) brain oscillations and that network correlations are not static (Iraji et al, 2021; Sakoğlu et al, 2010). The “dynamic” connectivity or dFNC approach utilizes smaller time windows (~2–10 s) to examine temporal scale changes, evaluates how the interactions of functional sources change over time, and tracks how brain networks vary over time producing different brain states.…”
Section: Introductionmentioning
confidence: 99%
“…The metrics, including coherence (Coh), imaginary coherence (imCoh), pairwise phase consistency (PPC), phase-locking value (PLV), PLI, weighted phase lag index (wPLI), and weighted phase lag index debiased (wPLI2), were compared in a recent study to test the reliability of resting-state MEG functional connectivity in schizophrenia (SZ). The article indicated that the reliability of these metrics varied greatly depending on the frequency band, network, and participant group examined (Candelaria-Cook and Stephen, 2020). Although there is no uniform standard for MEG resting-state functional connectivity, some identified factors should be considered: metrics (Colclough et al, 2016), frequency band (Meng and Xiang, 2016;Marquetand et al, 2019), and measurement duration (Marquetand et al, 2019).…”
Section: Resting-state Functional Connectivity Based On Meg Signalsmentioning
confidence: 99%